ISOLATION, SCREENING AND CHARACTERIZATION OF POTENT MARINE STREPTOMYCES SP. PM 105 AGAINST ANTIBIOTIC RESISTANT PATHOGENS - J, Thirumalairaj; SHANMUGASUNDARAM T,; SIVASANKARI K,; NATARAJASEENIVASAN K,; BALAGURUNATHAN R, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The present study aims to screen and isolate a promising strain of actinobacteria for the development of new antibiotic to fight against life-threatening infectious diseases. Methods: A total of 59 marine samples were collected from various marine ecosystem of India. About 242 actinobacterial strains were isolated by using starch casein agar medium. Preliminary screening of actinobacteria against eight antibiotic resistant pathogens was done using agar plug and cross streak method. Secondary screening was performed by well diffusion method. The potential actinobacteria were selected for bioactive metabolites production and it was partially purified by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Further, it was morphologically and physiologically characterized. Results: In preliminary screening, 18 actinobacterial strains were selected for their antibacterial activity against eight drug resistant pathogens adopting agar plug and cross streak method. The most promising strain PM105 was selected in secondary screening by performing agar well diffusion method. Actinobacterial strain PM105 showed most significant activity against both Gram-positive and Gram-negative antibiotic resistant pathogens with the concentration of 12.5 μg/ml. The maximum zone of inhibition was observed against three Gram-negative bacteria, such as Klebsiella pneumoniae (18.6±0.57), Pseudomonas aeruginosa (18.5±0.57) and Escherichia coli (18.4±0.57). Based on the morphological and physiological characteristics, potential strain PM105 was tentatively identified as Streptomces sp. Active compound was separated by TLC with Rf value of 0.7, and analyzed by HPLC, a major peak was observed at retention time of 4.779 minutes. Conclusion: The above findings revealed that antibacterial potential of actinobacteria from the marine sediment of India. Keywords: Marine sources, Actinobacteria, Antibiotic resistant pathogens, Bioactive metabolites, High-performance liquid chromatography.